Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/apt.17186
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: thiopurines in the multidrug era—time to rescue our memories over half a century of experience. Authors' reply

Abstract: LINKED CONTENT This article is linked to Rezazadeh Ardabili et al papers. To view these articles, visit https://doi.org/10.1111/apt.17128 and https://doi.org/10.1111/apt.17164

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In early studies, cases of nodular regenerative hyperplasia (NRH) of the liver (which may result in non-cirrhotic portal hypertension) were observed during TG therapy 46. However, in later studies, it was concluded that this was likely to be a dose-related adverse event 29 47–49. Furthermore, NRH was also seen in patients using other thiopurine derivatives (AZA/MP) and was potentially reversible after cessation of therapy, leading to a very mild disease course 47 50 51.…”
Section: Tg Versus Conventional Thiopurine Derivatives (Aza/mp)mentioning
confidence: 99%
“…In early studies, cases of nodular regenerative hyperplasia (NRH) of the liver (which may result in non-cirrhotic portal hypertension) were observed during TG therapy 46. However, in later studies, it was concluded that this was likely to be a dose-related adverse event 29 47–49. Furthermore, NRH was also seen in patients using other thiopurine derivatives (AZA/MP) and was potentially reversible after cessation of therapy, leading to a very mild disease course 47 50 51.…”
Section: Tg Versus Conventional Thiopurine Derivatives (Aza/mp)mentioning
confidence: 99%